Factors contributing to the rising cost of living for group M40 in Malaysia - Puteri Aida Sabrina Roslan; Humaida Banu Samsudin (Penerbit Universiti Kebangsaan Malaysia, 2024)
The rising cost of living is an increasingly pressing issue for every household in Malaysia. The middle-income group (M40) is also affected by the growing culture of indebtedness among them. This study examines the causes of the increased cost of living for this group based on two main factors: inflation and spending patterns. The trend in income growth and inflation is also observed and compared from year to year. This study found that inflation or the increase in prices of goods is almost always higher than income growth, making it difficult for the earned income to cover the cost of living. Meanwhile, for spending patterns, multiple regression analysis is conducted to identify the relationship between the demographic of M40 households and essential spending on food, transportation, and housing. The demographic factors considered are monthly income, household size, urban or rural location, and state. The relationship of the log-log linear regression model between spending and income indirectly illustrates the rigidity of essential spending for this group in relation to their income. Additionally, the rigidity of spending for all three essential items are normal. Household size, urban location, and state do not show a high regression factor, thus not significantly affecting their cost of living. Therefore, inflation was found to have a greater impact on the cost of living for the M40 group than their spending patterns.